Toward an Individual Binaural Loudness Model for Hearing Aid Fitting and Development - Pieper, Iko; Mauermann, Manfred; Kollmeier, Birger; Ewert, Stephan D. (Frontiers in Psychology, 2021)
The patient’s individual loudness perception plays an important role for hearing aid satisfaction and use in daily life. Hearing aid fitting and development might benefit from individualized loudness models (ILMs), enabling better adaptation of the processing to the individual needs. The central question is whether additional parameters are required for ILMs beyond non-linear cochlear gain loss and linear attenuation common to existing loudness models for hearing impaired (HI). Here, loudness perception in 8 normal hearing (NH) and 8 HI listeners was measured in conditions ranging from monaural narrowband to binaural broadband, to systematically assess spectral and binaural loudness summation and their interdependence. A binaural summation stage was devised with the empirical monaural loudness judgments serving as input. While NH showed binaural inhibition in line with the literature, binaural summation and its inter-subject variability was increased in HI, indicating the necessity for individualized binaural summation. Towards ILMs, a recent monaural loudness model was extended with the suggested binaural stage, and the number and type of additional parameters required to describe and to predict individual loudness was assessed. In addition to one parameter for the individual amount of binaural summation, a bandwidth-dependent monaural parameter was required to successfully account for individual spectral summation.